Gambaran Kebahagiaan pada Ibu yang Memiliki Anak Berkebutuhan Khusus Difabel, Austisme, Down Syndrome di UPT Resource Center Gresik - Lutfiana Prastika Devi; Muhimmatul Hasanah; Prianggi Amelasasih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Mother as an individual has the right to feel happiness in herself and her life even if she has a child with special needs. There is a process that a mother who has a child with special needs goes through to finally achieve happiness in her life. This study aims to describe the happiness of mothers who have children with special needs, including disabilities, autism, and down syndrome at UPT Resource Center Gresik. This study used a qualitative approach with a case study research type and used data collection techniques in the form of interviews, observation and documentation. Data analysis techniques use the Miles and Huberman models. The data credibility technique uses triangulation techniques and member checks. Based on the results of the research conducted by the researchers, it was shown that the three subjects were happy with their condition as mothers who have children with special needs including disabilities, autism, and down syndrome. The three subjects can establish relationships with the surrounding environment, be fully involved in their children's activities, find meaning in life, be optimistic about their children's future, and be resilient or be able to rise from the problems they face.